García Martínez, A. y Sáez Carreras, J. (1997). Del racismo a la interculturalidad. Competencia de la educación. Madrid: Narcea. 259 págs - Gloria Pérez Serrano (Universidad de La Rioja, 2013)
García Martínez, A. y Sáez Carreras, J. (1997). Del racismo a la interculturalidad. Competencia de la educación. Madrid: Narcea. 259 págs.